Characterization of microRNA Profiles in Pasteurella multocida-Infected Rabbits and Identification of miR-29-5p as a Regulator of Antibacterial Immune Response - Hu, Jiaqing; Li, Wenqiang; Qiao, Xibo; Li, Wenjie; Xie, Kerui; Wang, Yanyan; Huang, Bing; Zhao, Qiaoya; Liu, Lei; Fan, Xinzhong (Frontiers in Veterinary Science, 2021)
Pasteurella multocida is the pathogenic agent for a variety of severe diseases in livestock, including rabbits. MicroRNAs (miRNAs) participate in the immune response to the pathogen. Distinct miRNA expression patterns were explored in rabbit lung by small-RNA deep sequencing to assess dysregulated miRNAs during P. multocida infection. Totally, 571 miRNAs were screened, of which, 62 were novel, and 32 exhibited differential expression (DE). Of the 32 known DE-miRNAs, 13 and 15 occurred at 1 day and 3 days post-infection (dpi); and ocu-miR-107-3p and ocu-miR-29b-5p were shared between the two time points. Moreover, 7345 non-redundant target genes were predicted for the 32 DE-miRNAs. Putative target genes were enriched in diverse GO and KEGG pathways and might be crucial for disease resistance. Interestingly, upregulation of ocu-miR-29-5p suppresses P. multocida propagation and downregulates expression of epithelial membrane protein-2 (EMP2) and T-box 4 (TBX4) genes by binding to their 3′ untranslated region in RK13 cells. Thus, ocu-miR-29-5p may indirectly inhibit P. multocida invasion by modulating genes related to the host immune response, such as EMP2 and TBX4.